EKSPLORASI KEPUASAN DAN LOYALITAS PELANGGAN DALAM LAYANAN BANK DAN FINTECH: STUDI KUALITATIF - Fauzi, Armi Sulthon (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2022)
Banks have an important role in managing public finances both in terms of deposits or loans to improve people's lives. Along with the advancement of technology, the financial services business is also growing with the presence of financial technology which is expected to be able to provide various conveniences to users. However, financial technology (fintech) and banks have various types, so that customer satisfaction and loyalty are not known with certainty. For this reason, researchers want to explore customer satisfaction and loyalty to bank and fintech services with a qualitative approach. The purpose of this study was to explore customer satisfaction and loyalty in using bank and fintech services so that further actions can be identified to improve service quality. The method used is qualitative with data collection techniques through observation and interviews with 20 respondents who were randomly selected. In addition, this research was conducted in X district located in Central Java. The research data obtained will be analyzed in depth so that it is known that customer satisfaction is obtained from friendly, precise and agile customer service as well as the quality of the financial applications or technology offered both in terms of convenience and data security so that they are not easily hacked or account breaches. Then regarding loyalty, the majority of respondents persist with strong assumptions or paradigms regarding the convenience of a bank and also the many bank users they follow, such as BRI, Mandiri with fintech, each bank already has it as well as brimo livin, and so on that makes it easier users make transactions from anywhere and anytime.